(untitled) (Heritage, 2025)
This paper explores the profound implications of the application of artificial intelligence (AI) as an instrument of political surveillance in post-conflict societies, with a special focus on the cases of China, Israel, and the countries of the former SFRY, including the sensitive context of Kosovo and Metohija. The analysis adopts a multidisciplinary approach that combines security studies, political theory, digital ethics, and sociological perspectives to understand how AI transforms mechanisms of control, monitoring, and political decision-making. The paper argues that in post-conflict societies, AI is not merely a technological tool but a mechanism for restructuring state sovereignty, narrative control, and institutional dominance over political opponents. Special attention is given to the phenomena of digital authoritarianism, biometric surveillance expansion, algorithmic discrimination, and geopolitical use of data in the context of either stabilization or repression. Through a comparative analysis of China and Israel as leading exporters of AI-based surveillance systems and their diffusion into other parts of the world, including the Balkans, the paper highlights risks to human rights, democracy, and social cohesion. The paper concludes with recommendations for the development of ethical frameworks, regulatory policies, and international standards to curb the misuse of AI in fragile democracies and post-conflict zones.